Electromicrobiological concentration cells are an overlooked potential energy conservation mechanism for subsurface microorganisms - Marshall, Ian P. G. (Frontiers in Microbiology, 2024)
Thermodynamics has predicted many different kinds of microbial metabolism by determining which pairs of electron acceptors and donors will react to produce an exergonic reaction (a negative net change in Gibbs free energy). In energy-limited environments, such as the deep subsurface, such an approach can reveal the potential for unexpected or counter-intuitive energy sources for microbial metabolism. Up until recently, these thermodynamic calculations have been carried out with the assumption that chemical species appearing on the reactant and product side of a reaction formula have a constant concentration, and thus don't count towards net concentration changes and the overall direction of the reaction. This assumption is reasonable considering microorganisms are too small (~1µm) for any significant differences in concentration to overcome diffusion. However, recent discoveries have demonstrated that the reductive and oxidative halves of reactions can be separated by much larger distances, from millimetres to centimetres via conductive filamentous bacteria, mineral conductivity, and biofilm conductivity. This means that the concentrations of reactants and products can indeed be different, and that concentration differences can contribute to the net negative change in Gibbs free energy. It even means that the same redox reaction, simultaneously running in forward and reverse, can drive energy conservation, in an ElectroMicrobiological Concentration Cell (EMCC). This paper presents a model to investigate this phenomenon and predict under which circumstances such concentration-driven metabolism might take place. The specific cases of oxygen concentration cells, sulfide concentration cells, and hydrogen concentration cells are examined in more detail.